Sleep Quality and Sleep Behaviors in Varsity Athletes: A Pilot Study - Rebello, Lyndon J.; Roberts, Andrew W.; Fenuta, Alyssa M.; Cote, Anita T.; Bodner, Michael E. (Frontiers in Sports and Active Living, 2022)
Sleep hygiene practices may hinder university athletes from obtaining quality sleep to support health and performance. Qualitative aspects of sleep behaviors in athletes are not well described. We sought to provide a comprehensive evaluation of sleep quality and behaviours in varsity athletes using validated sleep questionnaires: the Athlete Sleep Screening Questionnaire (ASSQ) and the Athlete Sleep Behavior Questionnaire (ASBQ). Statistical significance was set at p<0.05. Sixty-three (n=63) athletes completed the questionnaires (54% female). Fifty-one percent met the threshold for adequate sleep (7+ hours) with 54% reporting being somewhat or very satisfied with sleep quality. Global scores for ASSQ Sleep Difficulty and ASBQ sleep behaviors were significantly correlated (r=0.31; p<0.05) as well as sleep duration and satisfaction (r=0.48 p<0.001). According to the ASSQ, 11% and 24% were classified as having severe or moderate sleep problems, respectively. The ASBQ categorized 62% as having ‘poor’ sleep behaviors. Notable sleep-influencing factors included frequent use of light-emitting devices before bed (90%), training later at night (after 7pm) (65%), and use of prescribed/over-the-counter sleep medication (19%). Half of university athletes do not meet thresholds for adequate sleep and a majority engage in sleep behaviors that do not promote adequate sleep. Some athletes may have clinical sleep problems and require referral. The ASBQ and ASSQ show promise in assessing clinical sleep problems and sleep behaviors in university athletes and may discern ‘cognitive and physiological arousal’ targets for use in educational workshops designed to promote optimal sleep hygiene in university athletes